Towards an interactive tool for music and dance: gestures, laban movement analysis and spectromorphology - Souza, Leandro; Freire Garcia, Sergio (Música Hodie, 2018)
The paper presents a real-time tool for the segmentation and analysis of body gestures, part of a larger se- tup for exploring music and dance in the contexts of electroacoustic composition, live-electronics and other interac- tive performances. The idea of gesture is the foundation of the proposed interactive strategies, and is discussed from different points of view. The current implementation uses the Max/Msp programming language and Kinect sensors. The segmentation of dance gestures is based on the inspection of the zero-crossings of the acceleration curve of ea- ch body joint. Concepts from Laban Movement Analysis are used to qualify the extracted gestures. Dance improvi- sations on Petrushka excerpts are the basis of a case study, where the relations between the music (tempo, pulses,instrumentation, character) and Laban Basic Actions are stressed.